Задача віртуального базування: математична модель та алгоритм розв’язання - Максимов, С. В. (ХНУРЕ, 2024)
The paper studies a virtual localization problem. A mathematical model of the problem using the phi-function technique is proposed in the form of nonlinear programming model. A solution strategy that combines algorithm of generating feasible starting points with nonlinear optimization procedure is developed. Testing of the proposed approach is carried out for two-dimensional case. The computational results are provided and illustrated with graphical illustrations.
Keywords: задача віртуального базування